2001
DOI: 10.1161/hh2201.100204
|View full text |Cite
|
Sign up to set email alerts
|

β 2 -Adrenergic Receptor Overexpression Increases Alveolar Fluid Clearance and Responsiveness to Endogenous Catecholamines in Rats

Abstract: Abstract-␤-Adrenergic agonists accelerate the clearance of alveolar fluid by increasing the expression and activity of epithelial solute transport proteins such as amiloride-sensitive epithelial Na ϩ channels (ENaC) and Na,K-ATPases. Here we report that adenoviral-mediated overexpression of a human ␤ 2 -adrenergic receptor (␤ 2 AR) cDNA increases ␤ 2 AR mRNA, membrane-bound receptor protein expression, and receptor function (procaterol-induced cAMP production) in human lung epithelial cells (A549). Receptor ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
93
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 40 publications
(43 reference statements)
1
93
0
Order By: Relevance
“…Thus, when delivered systemically, gene transfer is seen primarily to the pulmonary vascular endothelial cells, 6,7,9,35,36 whereas airway delivery results in transfer and expression in the epithelium. 9,10,35,37,38 One exception to this appears to be PEI, where it has been reported that intravenous delivery of PEI-DNA complexes can in fact lead to expression in alveolar epithelial type II cells. 3,39 By contrast, electroporation results in gene transfer to alveolar epithelial cells, as well as cells beyond the epithelial permeability barrier, including some smooth muscle and endothelial cells in focal areas of the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when delivered systemically, gene transfer is seen primarily to the pulmonary vascular endothelial cells, 6,7,9,35,36 whereas airway delivery results in transfer and expression in the epithelium. 9,10,35,37,38 One exception to this appears to be PEI, where it has been reported that intravenous delivery of PEI-DNA complexes can in fact lead to expression in alveolar epithelial type II cells. 3,39 By contrast, electroporation results in gene transfer to alveolar epithelial cells, as well as cells beyond the epithelial permeability barrier, including some smooth muscle and endothelial cells in focal areas of the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Lung proteins were obtained by homogenizing lung tissue collected from the peripheral 1-2 mm of each lobe as previously described (21,22). BAL was performed through a 20-gauge angiocath ligated into the trachea via tracheostomy.…”
Section: Methodsmentioning
confidence: 99%
“…Data supporting this conclusion come primarily from rat alveolar type II cells; however, the observation that alveolar type I cells have functional ion transporters and b 2 AR suggests similar regulation of ion transport in alveolar type I cells (5,56,57). Activation of b 2 -adrenergic receptor increases cellular Na,KATPase activity in alveolar epithelial cells in vitro and lung tissue (8,39,49,58). b 2 -adrenergic receptor-mediated shortterm regulation of Na 1 pumps occurs within minutes of receptor engagement via highly regulated recruitment of assembled Na,K-ATPases from intracellular compartments through phosphorylation of intermediary proteins and RhoA-kinase (49,59).…”
Section: Role Of Alveolar Epithelial B 2 -Adrenergic Receptorsmentioning
confidence: 95%
“…In the absence of agonist, the basal equilibrium favors the inactive conformation (6, 7). Spontaneous receptor activation explains the presence of basal b 2 AR-driven adenylyl cyclase activity in cells and observations of increased receptor function in the absence of agonist in models of b 2 AR overexpression (8)(9)(10). Engagement of the b 2 AR by a b 2 -agonist produces a conformational change shifting the equilibrium between receptor conformations toward the active form causing exchange of guanosine diphosphate (GDP) on Gsa for GTP and dissociation of Gsa from Gsbg.…”
mentioning
confidence: 99%